PRISEs (progesterone 5β-reductase and/or iridoid synthase-like 1, 4-enone reductases): Catalytic and substrate promiscuity allows for realization of multiple pathways in plant metabolism. (December 2018) - Schmidt, Karin; Petersen, Jan; Munkert, Jennifer; Egerer-Sieber, Claudia; Hornig, Michael; Muller, Yves A.; Kreis, Wolfgang
Abstract: PRISEs (progesterone 5β-reductase and/or iridoid synthase-like 1, 4-enone reductases) are involved in cardenolide and iridoid biosynthesis. We here investigated a PRISE (r At St5βR) from Arabidopsis thaliana, a plant producing neither cardenolides nor iridoids. The structure of r At St5βR was elucidated with X-ray crystallography and compared to the known structures of PRISEs from Catharanthus roseus (r Cr ISY) and Digitalis lanata (r Dl P5βR). The three enzymes show a high degree of sequence and structure conservation in the active site. Amino acids previously considered to allow discrimination between progesterone 5β-reductase and iridoid synthase were interchanged among r At St5βR, r Cr ISY and r Dl P5βR applying site-directed mutagenesis. Structural homologous substitutions had different effects, and changes in progesterone 5β-reductase and iridoid synthase activity were not correlated in all cases. Our results help to explain fortuitous emergence of metabolic pathways and product accumulation. The fact that PRISEs are found ubiquitously in spermatophytes insinuates that PRISEs might have a more general function in plant metabolism such as, for example, the detoxification of reactive carbonyl species. Graphical abstract: Substrate preferences of PRISEs can be altered by single amino acid mutations. Amino acids mutated in r At St5βR are highlighted together with the cofactor NADP+ and the substrate progesterone (in yellow). Image 1 Highlights: PRISEs are involved in cardenolide biosynthesis and iridoid biosynthesis. The crystal structure of a PRISE from a cardenolide/iridoid-free plant was determined. PRISEs share extremely similar three-dimensional structures. Substrate specificities of PRISES can be changed exchanging single amino acids. A distinction between progesterone 5β-reductase and iridoid synthase is not justified.